Reduction of Vibration in Concentrated Winding Permanent Magnet Synchronous Motor by Means of Skew Effects of Rotor. Issue 2 (April 2014) - Takahata, Ryoichi; Wakui, Shinichi; Miyata, Kenji; Noma, Keiji; Senoo, Masaharu
SUMMARY Global warming and the problem of successfully incorporating environmental safeguards are promoting the need for a more power‐efficient motor. Therefore, as a driving source, permanent magnet synchronous motors (PMSMs) with concentrated winding are widely used in a variety of fields. However, a PMSM with a concentrated winding generates more vibration than one with a distributed winding because of the radial electromagnetic force. This paper describes the effect of a new skewed rotor on the characteristics of a concentrated winding PMSM. We investigated this effect by three‐dimensional finite element method (3D FEM) analysis and measurement. We also demonstrate that the proposed rotor is effective in reducing the radial electromagnetic force without decreasing motor efficiency. © 2014 Wiley Periodicals, Inc. Electr Eng Jpn, 187(2): 33–43, 2014; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/eej.22400